TP8.2.9 Development & Evaluation of LapPass™: The Laparoscopic Passport. (28th October 2021) - Fong, Michelle; Treglohan, Jenny; Selvasekar, Chelliah; Sedman, Peter; Leeder, Paul; Francis, Nader
Abstract: Aims: Laparoscopic surgery is technically challenging and assessment of competency is necessary to ensure patient safety and guide training. Existing tools of assessment are mostly subjective, with a growing need for objective credentialing. LapPass™ was developed by a UK-based laparoscopic society as an accessible simulation assessment tool. The aim of this study was to report on its development and preliminary findings of usability and validity. Methods: LapPass™ consists of 4 tasks that test: bimanual dexterity, simulated appendicectomy, dissection and intracorporeal suturing. Participants were prospectively recruited from testing events. Online surveys were sent to assessors and participants to assess the usability, face and content validity of the tool. Options to respond were on a five-point Likert scale with ratings from strongly disagree (1) to strongly agree (5). Results: LapPass was launched and offered to trainees as free-of-charge assessment tool. 31 participants and 12 assessors took part. The 1st time pass rate for bimanual dexterity was 19/29 (65.5%), appendicectomy 13/23 (56.5%), dissection 20/27 (74.1%) and intracorporeal suturing 6/19 (31.5%). The mean scores for participants' usability and validity were 3.8 and 4.12 for bimanual dexterity; 3.96 and 4.37 for appendicectomy; 4.5 and 4.16 for dissection and 3.84 and 4.52 for intracorporeal suturing. Assessors' mean score of usability was 4.5 across all tasks. Assessors scored validity of bimanual dexterity 4.35, appendicectomy 4.42, dissection 3.71 and intracorporeal suturing 4.65. Conclusion: LapPass™ is a an accessible objective assessment tool for laparoscopic basic surgical skills with preliminary data to confirm its usability and face and content validity.